Using SuperPro Designer simulation in water and waste water treatment laboratory practices - Barreto Torrella, Dr.C. Sarah Isabel (Transformación, 2024)
This article aims to describe results of introducing simulation practice, using Super Pro Designer program, in laboratory practices of Water and Waste Water Treatment in Chemical Engineering career of the "Ignacio Agramonte Loynaz" University and designed teaching strategy for that purpose. The subject was studied to set its system of contents, frontier and environment, the relation to other subjects and the system, subsystem and learning dynamics as a whole. A system of laboratory practices and a teaching strategy to use the simulator SuperPro Designer were design. Learning and skills development were assessed through self-preparation control, performance in doing tasks, findings registered in the corresponding reports and application in other homework tasks. The set of activities designed favored students' independent work of students by presenting problematic situations in a nice graphical environment and under the teacher leadership continue varying operating conditions to evaluate results. The strategy fostered the horizontal and vertical connection of subjects of and the fulfillment of language, economy and ICT curricular strategies.
Keywords: simulation; teaching strategy; water softening; wastewater treatment